Extractive Industries The Management of Resources as a Driver of Sustainable Development - Addison, Tony; Roe, Alan (Oxford University Press, 2018)
"New initiatives recognize that resource wealth can provide a means, when properly used, for poorer nations to decisively break with poverty by diversifying economies and funding development spending. Extractive Industries: The Management of Resources as a Driver of Sustainable Development explores the challenges and opportunities facing developing countries in using oil, gas, and mining to achieve inclusive change. While resource wealth can yield prosperity it can also, when mismanaged, cause acute social inequality, deep poverty, environmental damage, and political instability. There is a new determination to improve the benefits of extractive industries to their host countries, and to strengthen the sector's governance. Extractive Industries provides a comprehensive contribution to what must be done in this sector to deliver development, protect often fragile environments from damage, enhance the rights of affected communities, and support climate change action. It brings together international experts to offer ideas and recommendations in the main policy areas. With a breadth of collective insight and experience, it argues that more attention must be given to the development role of extractive industries, and looks to the future to explain how action on climate change will profoundly shape the sector's prospects."